Layanan Psikoedukasi sebagai Upaya Pencegahan Perundungan di Sekolah Menengah Kejuruan - Cholilah, Inda Roziah; Prafitralia, Anisah; Firdaus, Rizqiana Adhe; Khafidul Ardhi, Muhammad Arin (Devotion : Jurnal Pengabdian Psikologi, 2023)
Cases of bullying in educational institutions and Islamic boarding schools are starting to occur. Educational institutions that should be safe places to build the student's character have been tarnished by the actions of some individuals due to cases of bullying. Not only do students experience anxiety as a result but also parents, teachers, and school principals. Therefore, preventive measures are needed so that bully can be minimized. The focus of this community service activity is to provide education about bullying aimed at class X, XI, and XII students of SMK 02 Islam 45 Ambulu Jember. Additionally, education is provided to stakeholders regarding efforts that can be undertaken to minimize the occurrence of bullying or when there are cases of bullying at school. The community service activities are carried out using the expository method, namely providing material and discussing with participants. This community service concludes that students enthusiastically participated in the activity until the end. Furthermore, an evaluation of psychoeducational activities was carry out through the Google Form, that inform the students understood the phenomenon of bullying after listening to explanations from the presenters.